Total acoustic transmission in a honeycomb network empowered by compact acoustic isolator - Haixiao Zhang; Rong Li; Yu Bao; Xiaoli Liu; Yiwei Zhang (Scientific Reports, 2023)
Abstract In recent years, acoustic metamaterials have exhibited extraordinary potential for manipulating the propagation of sound waves. However, it has been a challenge to control the propagation of sound waves through arbitrary pathways in a network. In this work, we designed a compact three-port isolator that can produce giant acoustic nonreciprocity by introducing actively controlled CNT films to the device without altering the geometric symmetry of it. This concept is subsequently applied to construct a 4 × 7 honeycomb network, in which, total transmission of sound wave in arbitrary pathway can be slickly achieved. Unlike the acoustic topological insulator, which only supports total transmission of arbitrary pathway in the band gap, our method provides more degrees of freedom and can be realized at any frequency. This ability opens up a new method for routing sound waves and exhibits promising applications ranging from acoustic communication to energy transmission.